2008
DOI: 10.1016/j.cirpj.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Metal forming progress since 2000

Abstract: Considerable changes have occurred in metal forming in the last decade. A record of these changes can be found in keynote papers presented by the members of the Scientific Technical Committee-Forming, at the CIRP Annual General Meeting each year. The keynote papers are excellent references on important developments in metal forming and are used as a reference, globally. Not only is this paper a compendium of most of the keynotes presented, but from 2001 onward, it has updates on new information on five keynote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(125 citation statements)
references
References 54 publications
2
120
0
3
Order By: Relevance
“…Therefore, a series of experiments of brass foils are being carried out to extensively investigate the influence of foil thickness, grain size and thickness to grain size ratio on material properties and springback behavior with a view to 09010-p. 5 [16,26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a series of experiments of brass foils are being carried out to extensively investigate the influence of foil thickness, grain size and thickness to grain size ratio on material properties and springback behavior with a view to 09010-p. 5 [16,26].…”
Section: Resultsmentioning
confidence: 99%
“…With its booming development, the demand on the accuracy of the metallic micro parts is elevating and has stimulated the research on the precision evaluation of micro-formed parts. In terms of micro bending process, the springback, caused by elastic recovery during unloading, is an important factor significantly affects the dimensional accuracy of micro-bent parts [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Research into resultant incrementally formed geometries has shown significant deviations from the planned geometries (Bambach et al, 2009), and that parameters including the forming velocity, the toolpath, the size of material and distance to supports and particularly the material springback of the sheet during forming all affect the geometric accuracy of the resulting shape. These geometric deviations are a key deterrent from the widespread take-up of the process (Jeswiet et al, 2008).…”
Section: The Problem Of Accuracymentioning
confidence: 99%
“…(2) where dp is the external diameter of the punch, dd is the internal diameter of the die, and t is the thickness of the specimen. The punch diameter variations result are shown in table 2 below.…”
Section: Punch-die Clearancementioning
confidence: 99%